Natural Resources and Their Development in Mahendragarh District of Haryana State - Roy, B B; Gupta, R K; Pandey, S (Annals of Arid Zone, 2016)
Mahendragarh district stretches from lat. 27° 47' to 28° 49' N and long. 75° 49' to 76°28' E and has an area of about 3474 sq. km. It consists of two bio-climatic regions, namely arid and .semi-arid zones. Maximum temperature of 41°_42°C sometimes rising to 47°C is recorded in the months of May-June, while the minimum temperature is recorded in December-January. The annual rainfall varies from 300 to 500 mm. The desertic soils with sandy to 'loamy sand texture are found in the arid part and soils belonging to sierozems are found in the semi-arid part. The main problems are shifting sand dunes, severe wind erosion, degraded pastures and scarcity of water. Recommendations for solving these problems have been made.